Integrating scientific and real-world evidence within and beyond the drug development process. (January 2012) - Epstein, Robert S; Sidorov, Jaan; Lehner, Jean-Pierre; Salimi, Tehseen
Newly developed healthcare treatments face a complex environment with many stakeholders who can accelerate or decelerate adoption, most notably the healthcare system payers. Understanding and integrating their needs earlier in clinical development will ensure a smoother transition from bench to bedside. This paper describes a new approach to shaping a more effective complementary process of 'value'' evidence generation both in and outside the clinical drug development process. We propose that biopharmaceutical companies consider bringing new solutions to market by marshaling cross-functional approaches to what we term an evidence-definition phase, evidence-generation phase and evidence-translation phase to drug and technology research and development. The organization of ongoing discovery, evaluation and translation with a 'real- world'' perspective should provide a more streamlined approach to ensure both regulatory and eventual marketplace success.